Applications of rg*b-open sets - Sindhu, G. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
Using the concept of rg*b -open set, we introduce and study the topological properties of rg*b -limit points, rg*b -derived sets, rg*b interior and rg*b-closure of a set, rg*b –interior points, rg*b -border, rg*b frontier and rg*b -exterior. Keywords: rg*b -limit point, rg*b -derived set, rg*b -interior, rg*b -closure, rg*b -interior points, rg*b -border, rg*b -frontier, rg*b -exterior.